Reconciling Indigenous Practices and Islamic Principles: A Comparative Analysis of the Fiqh Principles ‘Al-Dararu Yuzal’ and ‘Al-Adah Muhakkamah’ in the Panai Cultural Practice of Bugis Weddings - Amalia, Ainun (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2025)
This study aims to analyze the application of fiqh principles in the “Panai” tradition within Bugis marriage customs. Panai refers to a monetary payment that a male suitor is required to provide to the bride's family to cover wedding expenses. In the Bugis tradition, Panai is considered an essential component of the dowry, functioning almost as a precondition. Without Panai, marriages within this culture are unlikely to proceed. Over time, the meaning and significance of Panai have evolved, influenced by various social factors. It now serves as a measure of a woman's family’s social status, with its value increasing for women deemed beautiful, educated, or employed in prestigious professions such as civil service. The Bugis community upholds the culture of "siri," symbolizing dignity and honor, which makes marriage a sacred institution that reflects the family’s standing. Failure to meet Panai obligations can result in a loss of siri, making the provision of Panai a sacred duty for prospective grooms. While Islam teaches that the ideal dowry is one that minimizes difficulty, the practice of Panai raises questions about its compatibility with Islamic jurisprudence, which emphasizes facilitation and fairness. This study examines the Panai tradition through the lens of two fiqh principles: al-adah muhakkamah ("custom is authoritative") and ad-Darar Yuzal ("harm shall be removed "). Employing a qualitative methodology through desk research of relevant books and articles, this study explores the intersection of local traditions and Islamic jurisprudence. The findings aim to provide deeper insights into the conflict and reconciliation between cultural practices and Islamic legal principles in the context of Bugis marriage. Ultimately, this research contributes significantly to understanding the dynamics of marriage in Makassar Bugis culture and its broader implications for the application of Islamic jurisprudence in daily life.